Методологія підвищення ефективності оцінювання параметрів і характеристик радіоканалів корпоративних телекомунікаційних мереж - Михалевський, Дмитро Валерійович (Вінницький національний технічний університет, 2021)
Дисертаційна робота присвячена вирішенню актуальної науково-прикладної проблеми розроблення методології оцінювання параметрів та характеристик радіоканалів із врахуванням максимально-можливої кількості різноманітних факторів впливу на базі статистичних зв’язків між ними з метою підвищення технічної ефективності корпоративних телекомунікаційних мереж на етапах проектування та оптимізації. Для вирішення проблеми використано методи математичної статистики та регресійного аналізу результатів експериментальних досліджень, на основі яких, було розроблено методи оцінювання основних параметрів радіоканалів корпоративних телекомунікаційних мереж. Запропоновані методи враховують процеси поширення сигналів, внутрішні і зовнішні фактори впливу у корпоративних приміщеннях та призначені для забезпечення неперервної оптимізації покриття мережі радіодоступу, при мінімальних інформаційних втратах, та ефективного керування ресурсами для отримання оптимальних технічних показників радіоканалів. Для збільшення швидкодії обробки результатів під час початкової оптимізації мережі на етапах проектування, розроблено метод оцінювання гарантованої пропускної здатності радіоканалів корпоративних телекомунікаційних мереж для передачі різних типів трафіку. Вперше запропоновано інтегральні показники ефективності радіоканалів та дії факторів впливу для прогнозування інформаційних втрат в межах покриття мереж радіодоступу. Вперше запропоновано стохастичну модель флуктуацій основних параметрів радіоканалів на основі інтервалу розсіювання моделей регресій, яка, використовує статистичну імовірність і дисперсію. Вперше запропонована методологія оцінювання параметрів та характеристик радіоканалів корпоративних телекомунікаційних мереж, на основі узагальнених математичних моделей. Диссертация посвящена решению актуальной научно-прикладной проблемы разработки методологии оценки параметров и характеристик радиоканалов с учетом максимально-возможного количества различных факторов влияния на базе статистических связей между ними с целью повышения технической эффективности корпоративных телекоммуникационных сетей на этапах проектирования и оптимизации. Для решения проблемы использованы методы математической статистики и регрессионного анализа результатов экспериментальных исследований, на основе которых были разработаны методы оценки основных параметров радиоканалов корпоративных телекоммуникационных сетей. Предложенные методы учитывают процессы распространения сигналов, внутренние и внешние факторы влияния в корпоративных помещениях и предназначены для обеспечения непрерывной оптимизации покрытия сети радиодоступа, при минимальных информационных потерях, а также эффективного управления ресурсами для получения оптимальных технических показателей радиоканалов. Для повышения быстродействия оценивания, при начальной оптимизации сети, разработан метод оценки гарантированной пропускной способности радиоканалов корпоративных телекоммуникационных сетей для передачи различных типов трафика. Впервые предложено интегральные показатели эффективности радиоканалов и действия факторов влияния для прогнозирования информационных потерь в зоне действия сетей радиодоступа. Впервые предложено стохастическую модель флуктуаций основных параметров радиоканалов на основе интервала рассеивания моделей регрессий, которая использует статистическую вероятность и дисперсию. Получила дальнейшего развития теория оценивания параметров и характеристик радиоканалов корпоративных телекоммуникационных сетей на основе обобщенных математических моделей. This thesis is concerned with addressing the urgent applied-science challenge of developing a methodology for estimating radio channel basic parameters and characteristics corporate telecommunications networks considering influencing factors based on of statistical links between them in order to improve the technical efficiency of corporate telecommunication networks at the design and optimization stages. The purpose of this thesis is to resolve conflict between the need for increase in the data-transfer rate for improving the quality of information and communication services and the necessity for adaptive optimization of the network to reduce data loss through methods for estimating the radio channel parameters and characteristics in an environment of the limited radio-frequency resource and the influence of internal and external factors on the premises. This is achieved through a detailed study of hardware-based solutions for 5G and Wi-Fi wireless access technology and the processes appearing when sensing traffic in radio channels based the creation of a new approach to estimation of radio channel parameters and characteristics in order to improve the current methods and models of corporate telecommunications network design and optimization. Methods for estimating the basic parameters of radio channels in corporate telecommunications networks have been developed within the methodology. The suggested methods take into account the signal propagation processes, the internal and external influencing factors on the corporate premises; and they are intended to ensure that wireless access network coverage is continuously optimized with the minimum data loss, and the resources are effectively managed in order to obtain optimal performance characteristics of radio channels. A method for estimating the guaranteed bandwidth of radio channels for sending different types of traffic in corporate telecommunications networks has been developed in order to increase the speed of estimation during the initial optimization of the network. For the first time, the integrated factors of radio channel efficiency and the effect of influencing factors have been introduced to predict any data loss within wireless access network coverage. For the first time, a stochastic model of fluctuations of the main parameters of radio channels based on the scattering interval of regression models is proposed, which uses statistical probability and variance. The theory of estimation of radio channel parameters and characteristics in corporate telecommunications networks has been further developed based on generalized mathematical models. The implementation of the suggested methodology in a corporate telecommunications network consists in finding optimal radio channel parameters with the existence of external and internal influencing factors. Based on experimental studies of corporate telecommunications networks it was found that the implementation of the suggested methodology made it possible to achieve 9% increase in the estimation efficiency of the signal strength at the receiver input and 12% increase in the effective data-transfer rate using the transmitting-and-receiving equipment capabilities as compared with the existing methods and models. Moreover, applying the suggested methodology under the significant frequency resource load provided an opportunity for triple increase in the effective datatransfer rate and 8% enhancement of the signal level. Apart from that, it proved possible to double the area of guaranteed information and communication service delivery.
Методология повышения эффективности оценки параметров и характеристик радиоканалов корпоративных телекоммуникационных сетей
Methodology for Improving the Efficiency of Estimation of Radio Channel Parameters and Characteristics in Corporate Telecommunications Networks
Keywords: радіоканал; корпоративна телекомунікаційна мережа; потужність сигналу; пропускна здатність каналу; ефективна швидкість передачі інформації; параметри та характеристики; 5G; Wi-Fi; радиоканал; корпоративная телекоммуникационная сеть; мощность сигнала на входе приемника; пропускная способность канала; эффективная скорость передачи информации; факторы влияния; параметры и характеристики; radio channel; corporate telecommunication network; signal power; channel bandwidth; effective data rate; influencing factors; parameters and characteristics; 621.391.8